Oleuropein Protects Against Cerebral Ischemia Injury in Rats: Molecular Docking, Biochemical and Histological Findings - Mnafgui, Kais; Ghazouani, Lakhdar; Hajji, Raouf; Tlili, Abir; Derbali, Fatma; da Silva, Francisco Ivan; Araújo, Joabe Lima; de Oliveira Schinoff, Bianca; Bachega, José Fernando Ruggiero; da Silva Santos, Antônia Laíres; Allouche, Noureddine (Neurochemical research, 2021)
This study was designed to evaluate the underlying protective mechanisms of oleuropein involved in alleviating brain damage in a rat model of ischemic stroke. Male Wistar rats were divided into four groups; Control, stroke (MCAO), MCAO + clopidogrel (Clop) and MCAO + oleuropein (Ole). Results showed that the MCAO group evidenced significant brain edema (+ 9%) as well as increases of plasma cardiac markers such as lactate deshydrogenase (LDH), creatine kinase (CK-MB), fibrinogen and Trop-T by 11 %, 43%, 168 and 590%, respectively, as compared to the control group. Moreover, infarcted rats exhibited remarkable elevated levels of angiotensin converting enzyme (ACE), both in plasma and brain tissue, with astrocyte swelling and necrotic neurons in the infarct zone, hyponatremia, and increased rate of thiobarbituric acid-reactive substances (TBARS) by 89% associated with decreases in the activity of superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (Cat) by 51%, 44 and 42%, respectively, compared to normal control rats. However, MCAO rats treated with oleuropein underwent mitigation of cerebral edema, correction of hyponatremia, remarkable decrease of plasma fibrinogen and cardiac dysfunctional enzymes, inhibition of ACE activity and improvement of oxidative stress status in brain tissue. Furthermore, in silico analysis showed considerable inhibitions of ACE, protein disulfide isomerase (PDI) and TGF-β1, an indicative of potent anti-embolic properties. Overall, oleuropein offers a neuroprotective effect against ischemic stroke through its antioxidative and antithrombotic activities.